Pelestarian Identitas Budaya Melalui Upacara Adat Tulude di Masyarakat Nusu - Soleman Kelbulan (Kelompok Studi Mitra Skolastikat MSC PinelengINELENG, 2026)
This study examines the Tulude traditional ceremony in Desa Nusu, North Sulawesi, as part of cultural preservation that shapes community identity. Tulude is an annual tradition aimed at closing the old year, welcoming the new year with gratitude, and cleansing oneself from mistakes and negative influences. The study aims to describe the meaning, socio-cultural values, and the roles of traditional leaders, religious leaders, village officials, and the younger generation in maintaining Tulude. The research employs a qualitative approach with a descriptive method, collecting data through direct interviews with purposively selected informants. The findings indicate that the core activities of Tulude include worship/prayers of gratitude, the cutting of the traditional Tamo cake, and communal meals, reflecting religious, social, and cultural values while reinforcing solidarity and cultural identity. In conclusion, the sustainability of Tulude depends on the synergy of all parties involved, ensuring that this tradition remains alive, relevant, and passed on to future generations.